The influence of livefeed supplementation on growth and reproductive performance of guppies (Poecilia reticulata Peters, 1859) broodstock - Karaçuha, Ali; Aral, Orhan (Ege Univ, 2015)
In this study, the effects of feeding with five different feeds (Artemia sp., Daphnia sp., aquarium fish food + Artemia sp., aquarium fish food + Daphnia sp., aquarium fish food) on growth and fecundity of guppies broodstock (Poecilia reticulata Peters, 1859) with a mean initial weight of 0.924 g were investigated with three replications. The experiment was designed as five treatment with 15 groups except control and the trial lasted 12 weeks. Between the groups, fish fed with artemia supplement to aquarium fish food were obtained the best growth (weight, lenght, spesific growth rate) and fecundity performance. The results, among the groups, were statistically significant (p<0,05). However, a linear relationship was demonstrated between fecundity and weight (r=0.91) with length (r=0.90) of female broodstock fish.
Keywords: Daphnia; Poecilia reticulata; fecundity; gonad weight; Artemia; Poecilia reticulata; Artemia; Su piresi; Yavru verimi; Gonad ağırlığı